From fibrosis to granuloma: drug induced systemic sarcoidosis-like reaction after rituximab in a patient with primary Sjögren’s syndrome - Rui Rua Coelho; Sara Xavier Pires; José Ricardo Brandão; Inês Furtado (European Journal of Case Reports in Internal Medicine)
Sarcoidosis is a multisystemic syndrome characterized by non-caseous granulomatous inflammation, although necrotizing sarcoid granulomatosis is considered part of the spectrum of the disease. Drug induced sarcoidosis-like reaction (DISR) is a systemic granulomatous reaction, which is histopathologically identical to primary sarcoidosis - mostly described after the use of biologics like tumour necrosis factor alpha antagonists but also anti-CD20 (rituximab). The authors present the very rare case of a woman with a primary Sjögren’s syndrome (pSS) started on rituximab for disease control, which evolved with a 3-year indolent progressive systemic sarcoid reaction. There has been much speculation about the potential role of B cells in sarcoidosis. Findings show a decrease of B memory cells and an increase in naïve and active subsets of regulatory B cells in sarcoidosis patients, which resembles the repopulation with naïve B cells after treatment with rituximab. Moreover, granulomatous lymphocytic interstitial lung disease associated with common variable immunodeficiency and immune reconstitution syndrome in patients wirh human immunodeficiency virus show clinical similarities to DISR and can help unveil new cytogenic and physiologic pathways. To the authors’ knowledge this is the first report of a systemic sarcoidosis-like reaction with necrotizing granulomas following an anti-CD20 therapy and also the first described in a pSS patient - underlining the importance of recognizing necrotizing sarcoid granulomatous processes in the diferential diagnosis of patients with caseous inflammation. Although this is a very rare adverse effect, the case enhances the importance of actively searching for DISR after biologics, even in patients undergoing rescue on-label therapies, such as rituximab.